PENGARUH PEMBERIAN PROBIOTIK TEMBAN, BIOVET DAN BIOLACTA KEDALAM AIR MINUM TERHADAP PERFORMAN AYAM BROILER - Akhadiarto, Sindu (Jurnal Sains dan Teknologi Indonesia, 2009)
Probiotics is a feed additive in the form of life microorganisms that balance microorganism population in the digestive tract. This research was conducted to study the effect of addition of probiotics product into drinking water on performance. One hundred and fifty birds of day old chicks (DOC) of “Hybro-AM”strain were divided into 5 groups of treatments. The treatments were R0 (control diet+ drinking water without probiotics), R1 (R0 + Temban), R2 (R0 + Biolacta), R3 (R0 + Biovet), and R4 (commercial diet). Chicken were given diet and drinkingwater ad libitum. Feed intake, body weight gain and feed conversion were measured weekly and income over feed and cost (IOFC). Local feed (control died) and control with probiotics are feed with self formulation (R0, and R1 – R3). Thecontrol feed ingredient used are corn, rice brand, fish meal, hull soybean mea, palm oil, grit,DCP and premix. Results showed that treatments did not give significant effect (P>0,05) on feed intake, body weight gain and feed conversion. The result of Income Over Feed Cost (IOFC), shows that feed with control diet with probiotics Temban are best alternatif to pressure high price of feed and useable by farmer.